1560. Clinical Presentation of BK Virus-Associated Hemorrhagic Cystitis (HC) After Hematopoietic Cell Transplantation (HCT). (26th November 2018) - Imlay, Hannah; Xie, Hu; Leisenring, Wendy; Kimball, Louise; Pergam, Steven; Limaye, Ajit; Boeckh, Michael
Abstract: Background: BK polyoma virus (BKPyV) has been associated with hemorrhagic cystitis after HCT. Prior studies have examined risk factors for BKPyV-associated HC, but the characteristics of disease, including duration, common presentations, and the spectrum of clinical outcomes, have not been well described. Precise estimates of major clinical endpoints are critical to design clinical trials of novel prevention and treatment agents. Methods: We retrospectively analyzed HCT patients between 2007 and 2017. Subjects were included if they had macroscopic hematuria (Bedi grade ≥2), a positive urine BKPyV PCR, and at least one plasma BKPyV viral load available after platelet engraftment or Day 28 post-HCT. HC was defined by hematuria and positive urine BKPyV PCR; duration was determined by time to resolution of hematuria. Demographic data, baseline symptoms, and clinical outcomes (e.g., need for bladder irrigation, use of cidofovir) were reviewed. Results: BKPyV-HC developed in 149 HCT recipients (97.3% allogeneic, 73% myeloablative conditioning) at a median of 54 days post-transplant (IQR 40–73). Seven percent were co-infected with adenovirus at the time of diagnosis. Symptoms and outcomes are shown in Table 1. Of those with plasma viral load testing at the onset of HC, 91% (112/126) had BKPyV viremia with a median viral load of 2, 200 copies/mL (IQR 385–9, 300). Twenty-nine percent of the cohort received cidofovir. Conclusion: We describe the characteristics of BKPyV-associated HC in HCT recipients in the modern era of immunosuppression. BKPyV-associated HC is a morbid disease in need of improved management strategies; patient-centered estimates of outcomes are crucial for evaluating new agents. Disclosures: S. Pergam, Merck: Consultant, Consulting fee; Chimerix: Consultant, Consulting fee. A. Limaye, Novartis: Consultant, Consulting fee. M. Boeckh, Vir Biotechnology: Consultant and Grant Investigator, Consulting fee and Research grant; Chimerix Inc: Consultant, Grant Investigator and Investigator, Consulting fee, Research grant and Research support.